2024
DOI: 10.12911/22998993/176772
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Rice Management System on Soil and Rice Quality Index in Girimarto, Wonogiri, Indonesia

Muhammad Rizky Romadhon,
Mujiyo Mujiyo,
Ongko Cahyono
et al.

Abstract: Excessive chemical input in rice management systems has an impact on reducing soil quality and rice quality. The research that links soil quality with rice quality is needed to produce recommendations for improving rice cultivation to make healthy rice. This study aimed to determine the index values of soil and rice quality in organic, semi-organic, and conventional paddy fields as well as their relationship to formulate recommendations for land improvement. This research used descriptive explorative methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The medium class, organic C content, is at LMU 5, 12, and 21 (forests, rice fields, and plantations). The organic C content varies depending on land use (Romadhon et al, 2024), with higher levels found in plantation land use (Dadgar, 2018;Supriyadi et al, 2021), while research by Eleftheriadis et al (2018) shows the highest average organic C in forests, other research states that rainfed paddy fields have the organic C content is higher than in plantations (Rekwar, 2022). Rainfall affects the organic C content (F-count = 3.946; p-value = 0.024; N = 66).…”
Section: The Distribution Of Slaking Index In Various Soil Typesmentioning
confidence: 94%
See 1 more Smart Citation
“…The medium class, organic C content, is at LMU 5, 12, and 21 (forests, rice fields, and plantations). The organic C content varies depending on land use (Romadhon et al, 2024), with higher levels found in plantation land use (Dadgar, 2018;Supriyadi et al, 2021), while research by Eleftheriadis et al (2018) shows the highest average organic C in forests, other research states that rainfed paddy fields have the organic C content is higher than in plantations (Rekwar, 2022). Rainfall affects the organic C content (F-count = 3.946; p-value = 0.024; N = 66).…”
Section: The Distribution Of Slaking Index In Various Soil Typesmentioning
confidence: 94%
“…Organic C is one of the fundamental parameters in sustainable agriculture (Alaboz et al, 2022;Rahayu et al, 2024;Romadhon et al, 2024) and plays a role in nutrient availability, improving soil's physical, chemical, and biological properties (Farrasati et al, 2019;Meilani et al, 2023;Smith et al, 2013). The results of organic C analysis show that organic C at the research location is in the very low to medium category (Center for Research and Development of Agricultural Land Resources, 2009).…”
Section: The Distribution Of Slaking Index In Various Soil Typesmentioning
confidence: 99%
“…In line with research by Fadillah et al (2022), the increase in grain production in the inorganic system is shortlived because the decrease in soil physics health and the accumulation of chemical residues over a sufficiently long time can poison the plant. In contrast, in the organic system, soil health improves due to the use of more environmentally friendly organic materials (Romadhon et al, 2024).…”
Section: Soil Physics Healthmentioning
confidence: 99%